Low Skeletal Muscle Index Adjusted for Body Mass Index Is an Independent Risk Factor for Inflammatory Bowel Disease Surgical Complications. Issue 3 (1st August 2020) - Berger, Matthew; Yamada, Akihiro; Komaki, Yuga; Komaki, Fukiko; Cohen, Russell D; Dalal, Sushila; Hurst, Roger D; Hyman, Neil; Pekow, Joel; Shogan, Benjamin D; Umanskiy, Konstantin; Rubin, David T; et al.
Abstract: Background: This study aims to evaluate sarcopenia defined by skeletal muscle index (SMI) with cutoffs adjusted for sex and body mass index as a predictive marker for postoperative outcomes among individuals with inflammatory bowel disease. Methods: The SMI was measured using the cross-sectional computed tomography images at the lumbar spine. Multivariate logistic regression was performed to identify independent risk factors of postoperative complications. Results: Ninety-one patients were included in the study. In multivariate analysis, sarcopenia (odds ratio = 5.37; confidence interval: 1.04–27.6) was predictive of infectious postoperative complications. Conclusions: Sarcopenia as defined by the SMI is a predictor for 30-day postoperative infection complications in inflammatory bowel disease surgeries. Lay Summary: Skeletal muscle index can be measured using computed tomography scan images taken at the lumbar spine and when adjusted for sex and body mass index is a predictor for postoperative infection complications after inflammatory bowel disease surgeries.